METHOD FOR CALCULATING ORBITS OF NEAR–EARTH ASTEROIDS OBSERVED WITH TELESCOPE OMT-800 - Troianskyi, V. V.; Bazyey, A. A.; Kashuba, V. I.; Zhukov, V. V.; Korzhavin, S. A. (Одеські астрономічні публікації, 2014)
One of the frame processing techniques, as well as an example of further use of the obtained results to calculate an asteroid’s orbit are given in the present paper. The application of frame combination method to improve the telescope’s limiting magnitude is described.